“Obuchenie Sluzheniem” or “Service Learning”? A Discussion on the Conceptual Foundations of the Pedagogical Approach - V. S. Nikolskiy (Высшее образование в России)
This article contributes to the debate on the origins of the Service Learning pedagogical approach. It examines the controversy surrounding the identification of «Obuchenie Sluzheniem» and «Service Learning». The author comes to a number of conclusions. It is possible to state the superiority of the USSR in relation to the USA in the practice of introducing the approach requiring the integration of socially useful work and higher education. The Service Learning approach has become a significant part of the university landscape in the world, as the effectiveness of the approach has been proven in the course of numerous scientific studies. It is not correct to speak of a simple identity between indigenous service learning and the Western approach because of the great variety of existing implementation models. When talking about the intellectual foundations of Service Learning, K.D. Ushinsky should be mentioned along with J. Dewey. Thus, taking into account the similarities in terms of the theory and methodology of Obuchenie sluzheniem and Service Learning, the domestic approach has national historical-cultural and theoretical roots and specific features.